2021
DOI: 10.1093/pm/pnab263
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety, and Tolerability of Nabiximols Oromucosal Spray vs Typical Oral Long-Acting Opioid Analgesics in Patients with Severe Neuropathic Back Pain: Analysis of 6-Month Real-World Data from the German Pain e-Registry

Abstract: Objective To compare the effectiveness, safety, and tolerability of add-on nabiximols (NBX) oromucosal spray vs typical oral long-acting opioid (LAO) analgesics in patients with severe (± chronic) peripheral neuropathic back pain poorly responsive to other treatments. Methods Retrospective analysis of anonymized, propensity score–matched data from the German Pain e-Registry of adult outpatients who initiated NBX or LAO betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
(29 reference statements)
0
7
0
2
Order By: Relevance
“…These data are also consistent with reports that CBD is an antagonist at cannabinoid receptors 1 and 2, and can blunt the effects of THC [ 23 , 24 , 25 ]. Based upon the large number of studies that have reported that nabiximols (mixtures of approximately 1:1 THC:CBD) have antinociceptive properties, it was unexpected that we did not see a larger difference in anti-nociceptive potential with different ratios [ 14 , 15 , 16 , 17 ]. Our data suggest that there is little effect of CBD on reducing neuropathic pain, and that most of the reduction in pain can be attributed to THC, although CBD may help to augment the impact of THC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These data are also consistent with reports that CBD is an antagonist at cannabinoid receptors 1 and 2, and can blunt the effects of THC [ 23 , 24 , 25 ]. Based upon the large number of studies that have reported that nabiximols (mixtures of approximately 1:1 THC:CBD) have antinociceptive properties, it was unexpected that we did not see a larger difference in anti-nociceptive potential with different ratios [ 14 , 15 , 16 , 17 ]. Our data suggest that there is little effect of CBD on reducing neuropathic pain, and that most of the reduction in pain can be attributed to THC, although CBD may help to augment the impact of THC.…”
Section: Discussionmentioning
confidence: 88%
“…These products typically have varying ratios of THC:CBD but there are few studies that have investigated the optimal ratios of the two primary cannabinoids for treating medical conditions. Most studies that have investigated the interactions between these two cannabinoids have limited their scope to the 1:1 ratio typically found in nabixmols (Sativex ® ) [ 14 , 15 , 16 , 17 ]. While our data suggest that a 1:1 ratio of CBD to THC may not be optimal, there is a benefit of including CBD in combination with THC to reduce neuropathic pain, as lower levels of THC produced a reduction in sensitivity when CBD was included, this is especially true for the botanical extracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutische Effekte Laut Begleiterhebung einer Datenerhebung zur Verordnung zwischen 2017 und 2022 [6] und anderen Beobachtungsstudien [29,33] verbessern sich unter THC chronische Schmerzen, Schlaflosigkeit, Schwindel, Appetitlosigkeit und die Stimmung. ▶Tab.…”
Section: Wirkungen Und Nebenwirkungenunclassified
“…[29] verbessern sich unter THC chronische Schmerzen, Schlaflosigkeit, Schwindel, Appetitlosigkeit und die Stimmung. Tab.…”
unclassified